Synergy between dynamic covalent boronic ester and boron–nitrogen coordination: strategy for self-healing polyurethane elastomers at room temperature with unprecedented mechanical properties. Issue 1 (5th November 2020) - Song, Kai; Ye, Wujin; Gao, Xingchen; Fang, Huagao; Zhang, Yaqiong; Zhang, Qi; Li, Xueliang; Yang, Shanzhong; Wei, Haibing; Ding, Yunsheng
Abstract : Boron–nitrogen coordination in polyurethane elastomers enhances the dynamics of the boronic ester while introduces inter- and intra-molecular interactions, leading to mechanical robustness and excellent self-healing efficiency simultaneously. Abstract : Achieving mechanical robustness and highly efficient self-healing simultaneously at room temperature is always a formidable challenge for polymeric materials. Herein, a series of novel supramolecular polyurethane elastomers (SPUEs) are developed by incorporating dynamic covalent boronic ester and boron–nitrogen (B–N) coordination. The SPUEs demonstrate the highest tensile toughness (∼182.2 MJ m −3 ) to date for room-temperature self-healable polymers, as well as an excellent ultimate tensile strength (∼10.5 MPa) and ultra-high fracture energy (∼72 100 J m −2 ), respectively, owing to a synergetic quadruple dynamic mechanism. It is revealed that the B–N coordination not only facilitates the formation and dissociation of boronic ester at room temperature but also dramatically enhances the mechanical properties by the intermolecular coordinated chain crosslinking and intramolecular coordinated chain folding. Meanwhile, the B–N coordination and urethane hydrogen interaction also serve as sacrificial bonds, which rupture during stretching to dissipate energy and recover after release, leading to superior notch insensitiveness and recoverability. The SPUEs restore their mechanical robustness after self-healing at room temperature and the self-healing efficiency can be dramatically accelerated by surface wetting.